Nanomagnetic strontium ferrite nitrogen doped carbon (SrFe2O4-NC): Synthesis, characterization and excellent supercapacitor performance. (1st August 2022) - Al-Maswari, Basheer M.; Al-Zaqri, Nabil; Ahmed, Jahangeer; Ahamad, Tansir; Boshaala, Ahmed; Ananda, S.; Venkatesha, B.M.
Abstract: A novel nitrogen-doped carbon strontium ferrite (SrFe2 O4 -NC) nanocomposite with a particle size of 8–10 nm was obtained using the polymeric route. Bimetallic precursors based on iron (III) and strontium chloride were produced with urea and formaldehyde polymers and the precursors were heated at 700 °C in an inert atmosphere to form the SrFe2 O4 -NC nanocomposite with high surface area (approximately 170.4 m 2 /g). The prepared SrFe2 O4 -NC nanocomposite shows ferromagnetic nature with saturation magnetization value of approximately 15 emu/g. Using cyclic voltammetry (CV), galvanic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS), the supercapacitor capabilities of the SrFe2 O4 -NC nanocomposite were investigated in 5 M KOH. The SrFe2 O4 -NC nanocomposite electrode material demonstrates a higher specific capacitance of approximately 895 F/g. High performance of the supercapacitor could be due to their good cyclic stability, high charge - discharge rate, and high energy density. As a result, our focus was on the fabrication of cost-effective and higher performance electrode materials. Highlights: Search for new nanocomposite as supercapacitor. A new compound of nanomagnetic strontium ferrite nitrogen doped carbon (SrFe2 O4 -NC) was synthesized. The newly synthesized compound was subjected to characterization by various electrochemical studies. The supercapacitor of the compound was evaluated by cyclic voltammetry. The nanomagnetic strontium ferrite nitrogen doped carbon SrFe2 O4 -NC compound showed an excellent specific capacitance. The value of (Cs) is approximately 895 F/g at a scan rate of 50 mV/s from the (CV) studies with excellent GCD capacity.